Oxidative stress leads to the formation of esterified erythro- and threo-dihydroxy-fatty acids in HepG2 cells - Lilli Scholz; Luca M. Wende; Michel A. Chromik; Nadja Kampschulte; Nils Helge Schebb (Redox Biology)
Oxidative stress plays a central role in pathophysiology. To assess oxidative stress, sensitive methods are required to monitor the cellular damage caused by reactive oxygen species. Phospholipid-bound isoprostanes, such as 5-iPF2α-VI determined by liquid chromatography-tandem mass spectrometry (LC-MS/MS) are currently the best markers for oxidative stress. Here, we describe erythro- and threo-dihydroxy-polyunsaturated fatty acids (PUFA), the hydrolysis products of trans- and cis-epoxy-PUFA, as new biomarkers of oxidative stress in cells. This is demonstrated in four oxidative stress models in HepG2 cells using radical-forming tert-butyl hydroperoxide, glutathione peroxidase 4 inhibiting RSL-3, the redox cycling agent paraquat or rotenone blocking the electron transport chain. LC-MS/MS analysis following the liberation of esterified oxylipins by saponification unveiled in all oxidative stress models a strong formation of erythro- and threo-dihydroxy-PUFA. The levels increased concentration-dependently and correlated to isoprostane 5-iPF2α-VI formation. Among the positional isomers derived from linoleic acid, arachidonic acid and docosahexaenoic acid, those bearing the dihydroxy-group closest to the carboxy terminus were predominantly formed. Thus, the highest concentrations were found of erythro-5,6-DiHETrE and erythro-4,5-DiHDPE, which allowed a more sensitive detection of oxidative stress compared to 5-iPF2α-VI levels. The (erythro-) dihydroxy-PUFA are a new set of markers, which enable a more comprehensive analysis of oxidative stress, particularly when combined with simultaneous LC-MS/MS quantification of trans-epoxy-PUFA and isoprostanes.